2021
DOI: 10.1101/2021.09.03.458900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The m6A reader YTHDC2 is essential for escape from KSHV SOX-induced RNA decay

Abstract: The role m6A modifications have increasingly been associated with diverse set of roles in modulating viruses and influencing the outcomes of viral infection. Here we report that the landscape of m6A deposition is drastically shifted during KSHV (Kaposi Sarcoma Associated herpesvirus) lytic infection for both viral and host transcripts. In line with previous reports, we also saw an overall decrease in host methylation in favor of viral mRNA along with 5' hypomethylation and 3' hypermethylation. During KSHV lyti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…The m 6 A nuclear reader DC2 was also studied in KSHVinfected cells for its function in stabilizing RNAs, since many cellular mRNAs are degraded by KSHV endoribonuclease SOX (Macveigh-Fierro et al, 2022). This study found that the IL6 mRNA was m 6 A modified in its 3′UTR during KSHV lytic infection and that removal of this m 6 A restored susceptibility to SOX-mediated degradation.…”
Section: Herpesvirusesmentioning
confidence: 99%
“…The m 6 A nuclear reader DC2 was also studied in KSHVinfected cells for its function in stabilizing RNAs, since many cellular mRNAs are degraded by KSHV endoribonuclease SOX (Macveigh-Fierro et al, 2022). This study found that the IL6 mRNA was m 6 A modified in its 3′UTR during KSHV lytic infection and that removal of this m 6 A restored susceptibility to SOX-mediated degradation.…”
Section: Herpesvirusesmentioning
confidence: 99%